Industrial application of lean manufacturing / Wan Hasrulnizzam Wan Mahmood and Mohd Razali Muhamad - Wan Mahmood, Wan Hasrulnizzam; Muhamad, Mohd Razali (2008)
Global competition has led many manufacturing organizations to focus on productivity and quality improvement. One of the effective approaches used to achieve this, is through lean manufacturing. Lean manufacturing is defined as a system based on the philosophy of waste elimination which includes the removal of all non-value added activities from the process of delivering customers' requirement in a manner that delights the customers and ensures they maintain demands. The purpose of this paper is to discuss the related issues in implementing lean manufacturing and the development of this improvement strategy. The results of the study present findings from a company which has implemented lean manufacturing. It showed that many challenges were faced in their operation in order to establish lean manufacturing. The company has their own solution to manage the challenges while improving productivity.